1898 N.Y. Laws 582 - (:unkn) unknown (My University, 1898)
Ch. 212, art. 11, § 177: No body of men, other than the regularly organized corps of the national guard and militia and the troops of the United States except such independent military organizations as were on the twenty-third day of April, eighteen hundred and eighty-three, and now are, in existence, shall associate themselves together as a military company or organization, or parade in public with firearms in any city or town of this state.
Keywords: MILITIAS